Manipulative Identification Created by Preservice Mathematic Teacher - Rini Utami; Isti Hidayah; Stevanus Budi Waluya; Isnaini Rosyida (International Conference on Science, Education, and Technology, 2022)
Abstrak. Preservice mathematics teachers need to develop their competence, especially professional competence. Professional competence is related to the ability of preservice teachers to use mathematical manipulatives. Mathematics manipulatives can show real mathematical objects so that mathematics learning becomes meaningful. Preservice mathematics teachers can also design and create manipulatives as needed. This research is qualitative descriptive research. This study describes the types and uses of mathematical manipulatives made by preservice mathematics teachers in the Pekalongan University Mathematics Education Study Program. The results showed that there were 10 mathematical manipulatives with various uses, including understanding mathematical concepts, solving math problems, and playing math games. This mathematical manipulative can be used for learning mathematics, so it is necessary to test the effectiveness of the mathematical manipulative. These trials could involve schools and mathematics teachers. Lecturers should also analyze the difficulties of preservice mathematics teachers when making mathematical manipulatives so that appropriate assistance can be given according to the type of difficulty. Teachers also need to design learning in mathematics learning media courses that are more interesting so that mathematical manipulative products can be utilized by mathematics teachers and students gain in-depth knowledge of mathematical concepts.